The c.65‐2A>G splice site mutation is associated with a mild phenotype in Danon disease due to the transcription of normal LAMP2 mRNA. Issue 4 (3rd February 2016) - Cetin, H.; Wöhrer, A.; Rittelmeyer, I.; Gencik, M.; Zulehner, G.; Zimprich, F.; Ströbel, T.; Zimprich, A.
Abstract : Danon disease (DD) is a rare X‐linked multisystem disorder caused by mutations of the LAMP2 gene and characterized by intellectual disability, skeletal myopathy and cardiomyopathy. The survival time is severely reduced. Contrasting with the usual disease course, we report on a family with an exceptionally mild phenotype of DD despite having two potentially damaging LAMP2 mutations. Using RNA‐Seq analysis, we showed that a c.65‐2A>G splice site mutation results in the tissue‐specific production of four different transcripts including the full‐length mRNA in muscle tissue but not in leukocytes. We confirmed our results by immunohistochemistry and immunoblotting, showing the detection of LAMP2 protein only in muscle. The second mutation (c.586A>T, p.T196S) has been reported before to have an uncertain clinical significance. In our patients, however, neither of the two mutations seem to have a high enough functional impact to cause a severe phenotype. Overall, our study reveals that alternative splicing is a potential mechanism in DD with underlying splice site mutations of the LAMP2 gene in order to rescue the full‐length mRNA. Moreover, our report of a mild phenotype complements the DD spectrum, which is of great importance for a rare disease suspected to be underdiagnosed. Abstract :